Effect of Sulfuric Acid (H₂SO₄) Scarification on Seed Dormancy Breaking and Germination of Soursop (Annona muricata L.) - Eko Wahyudi; Melati Hutabarat; Elza Zuhry; Elisa Apriliani; Dian Rakhmad; Nurbaiti Nurbaiti; Anthony Hamzah; Chandra Gunawan; Yunandra Yunandra (Green Engineering Society, 2026)
Soursop (Annona muricata L.) is a tropical fruit plant with high economic value; however, its cultivation is limited by seed dormancy, which delays germination. This study aimed to determine the most effective sulfuric acid (H₂SO₄) concentration for breaking seed dormancy and improving seed viability of soursop. The experiment was conducted at the Greenhouse and Plant Breeding Laboratory, Faculty of Agriculture, Universitas Riau, and implemented using a completely randomized design with four treatments: 0% (control), 70%, 75%, and 80% H2SO4 concentration. Each treatment was repeated five times. A total of 20 experimental units were obtained, each consisting of 25 seeds, for a total of 500 seeds used in the experiment. The results indicated that sulfuric acid treatment significantly affected most germination parameters. Seeds soaked in a 75% sulfuric acid solution exhibited the fastest germination time (28.40 Day After Planting), the highest germination percentage (88.80 %), and the strongest seed vigor (5.55%). These findings suggest that chemical scarification with 75% H₂SO₄ for 30 minutes can serve as a practical and efficient pre-sowing treatment to improve seedling establishment in soursop propagation.